Some instructional materials for developing inferential skills among grade six pupils - Maturana, Carita Pestano 1941- (1978)
This study is an attempt to make a proposed set of exercises for developing inferential skills for grade six pupils similar to the culture-bound Reading for Understanding Skill Builder Series. The exercses were taken from graded textbooks, workbooks and programmed materials ranging from English, character education, social studies, science, mathematics, agriculture and health. The multiple choice type of test was used for the 60 exercises. After being administered to pupils and the scores evaluated, some of the exercises were revised and were analyzed. The items finally selected were arranged from the easiet to the most difficult.